A longitudinal corpus study of syntactic complexity development in L2 writing / Nur Najah Radhiah Zainal Abidin - Nur Najah Radhiah, Zainal Abidin (2017)
This research explores syntactic complexity differences of L2 writing in the Longitudinal Corpus of Languaculturer Narrative Texts (Chau, 2015). This research aims to study syntactic complexity development in L2 writing based on the idea that learner language should be described in its own right. This study uses the L2 Complexity Analyzer (Lu, 2010) to process the written English sample by the participants and provides 14 indices as a measure of syntactic complexity. The scores from L2 Syntactic Complexity Analyzer were analyzed using repeated measures ANOVA, establishing statistical differences of 14 indices between the four different points in time.